Data Envelopment Analysis Approach for Efficiency Comparison of Banking System - Rendra Erdkhadifa; Risdiana Himmati (Institute of Computer Science (IOCS), 2022)
This study aims to calculate the level of banking efficiency that needs to be known to be associated with the performance of the banking management macro and micro variable. So banking industry in practice can arrange a program to increase efficiency and to anticipate the influence of anything that can makes banking will be lost .Bank with a good the efficiency in general is able to provide good service for customer. Efficiency of bank usually set pricing with the form of the high interest margin .The variables input used in this research is amount of labor .And the output to calculate efficiency are interest income of the money and the amount of funds which has been distributed. Then, comparing two different principle banking between bank syariah mandiri and bank mandiri. By using the method of measurement efficiency with DEA CCR, in two banks was efficient in some specified time. And then using DEA aggressive appears that the efficiency that tends to look the differences between DMU from both banks. From the, observation bank Syariah mandiri is much better because it can reach effieciency 12nd DMU. If calculating unefficiency that bank syariah mandiri also is better than bank mandiri.